Frequency-dependent acceleration of relaxation in mammalian heart: a property not relying on phospholamban and SERCA2a phosphorylation - Valverde, Carlos Alfredo (2005)
An increase in stimulation frequency causes an acceleration of myocardial relaxation (FDAR). Several mechanisms have been postulated to explain this effect, among which is the Ca²⁺–calmodulin-dependent protein kinase (CaMKII)-dependent phosphorylation of the Thr¹⁷ site of phospholamban (PLN). To gain further insights into the mechanisms of FDAR, we studied the FDAR and the phosphorylation of PLN residues in perfused rat hearts, cat papillary muscles and isolated cat myocytes. This allowed us to sweep over a wide range of frequencies, in species with either positive or negative force–frequency relationships, as well as to explore the FDAR under isometric (or isovolumic) and isotonic conditions. Results were compared with those produced by isoprenaline, an intervention known to accelerate relaxation (IDAR) via PLN phosphorylation. While IDAR occurs tightly associated with a significant increase in the phosphorylation of Ser¹⁶ and Thr¹⁷ of PLN, FDAR occurs without significant changes in the phosphorylation of PLN residues in the intact heart and cat papillary muscles. Moreover, in intact hearts, FDAR was not associated with any significant change in the CaMKII-dependent phosphorylation of sarcoplasmic/endoplasmic Ca²⁺ ATPase (SERCA2a), and was not affected by the presence of the CaMKII inhibitor, KN-93. In isolated myocytes, FDAR occurred associated with an increase in Thr¹⁷ phosphorylation. However, for a similar relaxant effect produced by isoprenaline, the phosphorylation of PLN (Ser¹⁶ and Thr¹⁷) was significantly higher in the presence of the β-agonist. Moreover, the time course of Thr¹⁷ phosphorylation was significantly delayed with respect to the onset of FDAR. In contrast, the time course of Ser¹⁶ phosphorylation, the first residue that becomes phosphorylated with isoprenaline, was temporally associated with IDAR. Furthermore, KN-93 significantly decreased the phosphorylation of Thr¹⁷ that was evoked by increasing the stimulation frequency, but failed to affect FDAR. Taken together, the results provide direct evidence indicating that CaMKII phosphorylation pathways are not involved in FDAR and that FDAR and IDAR do not share a common underlying mechanism. More likely, a CaMKII-independent mechanism could be involved, whereby increasing stimulation frequency would disrupt the SERCA2a–PLN interaction, leading to an increase in SR Ca²⁺ uptake and myocardial relaxation.